2021
DOI: 10.1007/s10924-021-02244-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curing Temperature on Mechanical Properties of Bio-phenolic/Epoxy Polymer Blends

Abstract: Nowadays, researchers continue studies for alternative materials to replace the redundant petroleumbased products. The combination of various polymer mixture process mainly from bio-polymer material as a matrix property could reduce the dependence over petroleum-based polymer, thus the dangerous residue waste from the synthetic polymer in the fabrication process could be eliminated and produce better composite material with lower cost and high performance of composite material in numerous applications. In this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…In the 0° direction, the tensile strength increased by 5.82%, but the tensile modulus decreased by 12.54%. However, the flexural strength, flexural modulus, and shear strength in the 45° direction showed little change, and the test results are in good agreement with Ismail’s [ 41 ] results.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In the 0° direction, the tensile strength increased by 5.82%, but the tensile modulus decreased by 12.54%. However, the flexural strength, flexural modulus, and shear strength in the 45° direction showed little change, and the test results are in good agreement with Ismail’s [ 41 ] results.…”
Section: Resultssupporting
confidence: 86%
“…The results showed that the hardness and flexural strength of both CFRP and GFRP were improved, but the mechanical strength of CFRP was not significantly improved, and that of GFRP was slightly improved. Ismail et al [ 41 ] investigated the effect of curing temperature on the mechanical properties of bio-phenolic/epoxy polymer blends. The results showed that the tensile strength of the blends was proportional to the curing temperature, and the tensile modulus was inversely proportional to the curing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the increase in bioresin content has led to the % elongation at break of the samples due to the presence of aliphatic chains of bio-resin, which imparts flexibility to the polymeric matrix. Similar results were reported by A. S. Ismail et al with blending bio-phenolic resin with epoxy [21,22].…”
Section: Tensile Testsupporting
confidence: 90%
“…On the other hand, it also enables a precise layup of the impregnated strand on the rotating mandrel, i.e., the previous layer without any gaps or overlapping [24,25]. Due to the deposition of multilayers, there is a cyclic profile of tem-perature in the FW process, which is considerably related to fabrication and, consequently, with the curing kinetics of epoxy resin systems, curing temperature, and strength of the manufactured parts [26][27][28][29][30][31][32][33][34]. In parallel with the study of the process parameters effect, a few thermal analyses (TGA and DSC) of epoxy resin and composite specimens have been measured to determine the range of curing temperature, degradation of the composites, glass fiber weight percentage, and volatile materials, i.e., thermal and dimensional stability of composite pipes.…”
Section: Introductionmentioning
confidence: 99%